2017
DOI: 10.4103/ijmr.ijmr_1339_15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence & factors associated with depression among schoolgoing adolescents in Chandigarh, north India

Abstract: Background & objectives:Depression among adolescents is a rising problem globally. There is a need to understand the factors associated with depression among adolescents. This study was conducted to ascertain the prevalence of depressive disorders and associated factors among schoolgoing adolescents in government and private schools in Chandigarh, India.Methods:A cross-sectional study was conducted among 542 randomly selected schoolgoing adolescents (13-18 yr), from eight schools by multistage sampling techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 22 publications
(47 reference statements)
10
36
1
Order By: Relevance
“…In contradiction to the findings reported by Singh et al .,[27] depression was found to be three times higher among adolescents studying in private schools. This might be attributed to the fact that in Indian scenario, the study culture is more competitive and hectic in private schools when compared with government ones, which thereby leads to stress among students, and on a long-term it may indirectly lead to depression.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contradiction to the findings reported by Singh et al .,[27] depression was found to be three times higher among adolescents studying in private schools. This might be attributed to the fact that in Indian scenario, the study culture is more competitive and hectic in private schools when compared with government ones, which thereby leads to stress among students, and on a long-term it may indirectly lead to depression.…”
Section: Discussioncontrasting
confidence: 99%
“…However, no such association has been observed in other previous studies. [13172729] In contradiction to that, some other previous studies had reported more depressive symptoms among students studying in higher standards and had accounted it to academic pressure. [43031]…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Some studies showed the association of academic stress with suicide (Arun & Chavan, 2009), substance use (Leonard et al, 2015), lower subjective well-being, risky behavior (smoking and drinking) and lower quality of relationship with parents and peers (Lemma et al, 2014), higher risk of depression (Jayanthi et al, 2015). Similarly, if adolescent students were not satisfied with their academic performance and/or parental dissatisfaction, they were more likely for depression (Verma et al, 2017;Singh et al, 2017). Unfortunately, in the current situation, the COVID-19 pandemic has further affected the academic area of students and it may cause for the escalation of stress among the Nepali adolescent students.…”
Section: Introductionmentioning
confidence: 99%